Regulation of Cancer-Associated miRNAs Expression under Hypoxic Conditions - Jesús Valencia-Cervantes; Martha Patricia Sierra-Vargas (Analytical Cellular Pathology)
Solid tumors frequently experience hypoxia or low O2 levels. In these conditions, hypoxia-inducible factor 1 alpha (HIF-1α) is activated and acts as a transcription factor that regulates cancer cell adaptation to O2 and nutrient deprivation. HIF-1α controls gene expression associated with various signaling pathways that promote cancer cell proliferation and survival. MicroRNAs (miRNAs) are 22-nucleotide noncoding RNAs that play a role in various biological processes essential for cancer progression. This review presents an overview of how hypoxia regulates the expression of multiple miRNAs in the progression of cancer cells.